Pengaruh Lingkungan Kampus terhadap Motivasi Belajar Mahasiswa - Isda Nurul Azkhiya; Rizqy Naufal Fatichin; Tita Puspitasari; Sri Mulyeni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The campus atmosphere significantly affects students' motivation for learning, influencing their academic experiences, mental health, and social relationships. This study explores how the campus environment impacts students' learning motivation through a literature review approach. The campus atmosphere is a multifaceted concept that includes physical, educational, and social aspects. A conducive physical environment, with well-maintained facilities and adequate learning spaces, enhances students' comfort and focus. The educational environment, particularly the interaction between lecturers and students, teaching methods, and institutional support, plays a key role in students' motivation and involvement. Additionally, the social environment, which includes friendships and a sense of belonging to the campus community, fosters intrinsic motivation and positive learning attitudes. Using a literature review approach, this study analyzes academic sources such as peer-reviewed journals, theses, and scholarly articles on the campus environment and student motivation. The findings indicate that a supportive campus atmosphere enhances students' motivation to learn, while a negative atmosphere can lead to decreased motivation and poor academic involvement. Universities should focus on creating and maintaining a supportive campus atmosphere to improve students' learning motivation and academic success.